2009
DOI: 10.1111/j.1463-5224.2009.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconjunctivitis associated withToxoplasma gondiiin a dog

Abstract: A 12-year-old Pug presented with a 3-mm corneal mass OD. The dog was currently being treated for keratoconjunctivitis sicca (KCS) and pigmentary keratitis OU. A superficial keratectomy followed by cryotherapy was performed OD. A histopathologic diagnosis of epithelial dysplasia and suppurative keratitis was made and the lesion resolved. Two months later, a yellow/tan conjunctival mass, diffuse chemosis and conjunctival thickening was discovered OD. Necrotizing conjunctivitis with protozoal parasites was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…In addition, treatment with diclazuril dosed at either 65 or 120 mg/kg demonstrated clinical protection against maternal hepatitis and fetal toxoplasmosis in a mouse challenge study (Oz & Tobin, ). Future therapeutic approaches may include triazines for treatment of toxoplasmosis in veterinary species (Swinger, Schmidt, & Dubielzig, ).…”
Section: Clinical Efficacy Of Triazinesmentioning
confidence: 99%
“…In addition, treatment with diclazuril dosed at either 65 or 120 mg/kg demonstrated clinical protection against maternal hepatitis and fetal toxoplasmosis in a mouse challenge study (Oz & Tobin, ). Future therapeutic approaches may include triazines for treatment of toxoplasmosis in veterinary species (Swinger, Schmidt, & Dubielzig, ).…”
Section: Clinical Efficacy Of Triazinesmentioning
confidence: 99%
“…In one case report, a 12‐year‐old pug was presented with KCS, pigmentary keratitis OU and a corneal mass, caused by Toxoplasma gondii (Swinger et al . ). A recently published study reported on the presence of CP in pugs (Labelle et al .…”
Section: Discussionmentioning
confidence: 97%
“…The morphology of the protozoal zoites was compatible with what is described for T gondii , although other protozoa, such as Neospora sp. or Sarcocystis spp., could not be entirely excluded . Serology for T gondii (IgG/IgM IFA; TVMDL, College Station, TX, USA) and Neospora caninum (IFA; TVMDL) were negative.…”
Section: Discussionmentioning
confidence: 99%
“…Canine corneal protozoal infections without systemic involvement are rarely reported in the veterinary literature and documented agents include T gondii , Leishmania mexicana , and amoebas . A recent case series listed 5 cases of ocular protozoal infections in dogs from 1998 to 2014, 2 supportive of T gondii . Both cases were small breed dogs receiving chronic topical immunosuppressive therapy for ocular surface disease that presented for a mass‐like lesion on the cornea or conjunctiva.…”
Section: Discussionmentioning
confidence: 99%